Allowance and tightness in language: (Cemitic Comparative study) - Abd, Yousry Abbas (Al-Adab Journal, 2020)
Our research deals with the tagged (Allowance and tightness in language-Cemitic Comparative study), to show the similarities and differences in the allowance and types in Semitic languages are the subject of study (Arabic, Syriac, Hebrew, Akkadian, Aramaic urban), and knowledge of grammatical and linguistic halls between them through comparison between them Through the presentation of each language separately and to reach the most common uses of wildcards and types in Semitic languages.